2022
DOI: 10.1055/s-0042-1743148
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Change Affects Flexural and Thermal Properties of Fused Deposition Modeling Poly(Lactic Acid) and Compression Molding Poly(Methyl Methacrylate)

Abstract: Objective Polylactic acid (PLA) is one of the most widely used materials in three-dimensional (3D) printing technology due to its multiple advantages such as biocompatibility and biodegradable. However, there is still a lack of study on 3D printing PLA for use as a denture base material. The goal of this study was to compare 3D printing PLA to traditional poly(methyl methacrylate) (PMMA) as a denture basis. Materials and Methods The PMMA (M) and PLA (L) specimens were fabricated by compression moldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The previous studies showed that the 3D-printed PLA by FDM has lower exural strength than PMMA 11,23 . Additionally, the exural strength of the milled PLA was reported to be lower 24 than that of milled PMMA was reported by the other studies 25,26 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The previous studies showed that the 3D-printed PLA by FDM has lower exural strength than PMMA 11,23 . Additionally, the exural strength of the milled PLA was reported to be lower 24 than that of milled PMMA was reported by the other studies 25,26 .…”
Section: Discussionmentioning
confidence: 96%
“…According to Charasseangpaisarn et al, the exural properties of 3D-printed PLA by fuse-deposition modeling (FDM) were lower than that of conventional heat polymerized PMMA. Furthermore, the exural properties also decreased when evaluated in the high temperature environment 11 . Thus, the improvement of thermal properties is necessary for using PLA as long term temporary or permanent restorative material.…”
Section: Introductionmentioning
confidence: 98%
“…However, 0 degree was recommended by the manufacturer to make the load applied perpendicular to printing layer orientations as the specimens (full printed teeth no plate or disc specimens) placed on the testing machine with the same printing direction (►Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with subtractive milling, printing wastes less material. 3,4 Multiple dentures can be made at once using printing. 3 Complex patterns can be produced using printing but milling occasionally has that limitation.…”
Section: Introductionmentioning
confidence: 99%
“…After many trial experiments performed using polylactic acid (PLA) filament, which does not produces satisfactory micro-features, PMMA was opted for FFF 3D Printing. PMMA has far better mechanical and thermal properties than PLA, such as high impact, tensile and flexural strength (Alhotan et al , 2021; Charasseangpaisarn et al , 2022). It has higher thermal diffusivity (0.13 mm2/s), glass transition temperature (110 ° C) and thermal conductivity (0.19 W/m-K).…”
Section: Methodsmentioning
confidence: 99%